2016
DOI: 10.1108/bfj-10-2015-0386
|View full text |Cite
|
Sign up to set email alerts
|

A model for measuring technology capability in the agrifood industry companies

Abstract: Access to this document was granted through an Emerald subscription provided by emeraldsrm:374558 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The technological capacity involves a series of financial and human resources to achieve efficiency [11]. Technological capacity encompasses the practical and theoretical knowledge that will allow a company to improve and develop new products [12,13]. New technologies have important implications in open innovation processes for SMEs, since with this organizational link, they can meet customer expectations and achieve more excellent corporate financial performance [14].…”
Section: Introductionmentioning
confidence: 99%
“…The technological capacity involves a series of financial and human resources to achieve efficiency [11]. Technological capacity encompasses the practical and theoretical knowledge that will allow a company to improve and develop new products [12,13]. New technologies have important implications in open innovation processes for SMEs, since with this organizational link, they can meet customer expectations and achieve more excellent corporate financial performance [14].…”
Section: Introductionmentioning
confidence: 99%
“…This understanding is shared by De Mori et al (2016), who focused on the analysis of technological capability in agribusiness system companies, in which technology capability present an important role in achieving efficiency in a company's production process and degree of innovativeness. Directing the lens to the transaction capability Guan and Ma (2003) indicated that this is a significant component of the innovation capability.…”
Section: Discussionmentioning
confidence: 99%
“…TC play an important role in achieving organizational efficiency and a degree of innovativeness. They are associated with the skills and knowledge necessary for an organization to absorb, use, adapt, develop, and transfer technologies [ 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…TC may play a key role in enhancing the effectiveness of a healthcare entity in terms of innovation and providing health services. TC are generally related to the knowledge and skills necessary for an individual to develop, use, adapt, absorb, and transfer technology [ 38 ]. A company’s technology can be thought of as part of the extensive knowledge, techniques, systems, and tools available to produce, distribute, and use goods and services at the end destination.…”
Section: Literature Reviewmentioning
confidence: 99%